Pengaruh Kesadaran Pajak, Tarif Pajak, dan Pelayanan Pajak Terhadap Kepatuhan Wajib Pajak (Studi Kasus pada UMKM yang terdaftar di KPP Pratama Batu) - Zufly Amrullah Hadi; Afifudin Afifudin; Siti Aminah Anwar (Universitas Islam Malang, 2023)
The Covid-19 Virus pandemic or often known as the Corona Virus has a considerable impact on economic sustainability, especially in the field of taxation. Taxes are the main source of state revenue which accounts for around 70% of all tax revenues (Salamah, 2020). The purpose of this study is to determine the effect of tax awareness, tax rates, and tax services on taxpayer compliance (Case study on MSMEs registered at KPP Pratama Batu). The population in this study is individual MSME taxpayers who are registered in KPP Pratama batu. In this study using the saturated sample technique so that the number of samples used in this study amounted to 100 taxpayers. The results showed that the tax awareness variable negatively affects taxpayer compliance, while the tax rate and tax service variables have a positive effect on taxpayer compliance.Keywords: Tax awareness, tax rate, tax service, KPP Pratama Batu